Gambaran Tingkat Pengetahuan Pelajar SMP Negeri 4 Seram Barat tentang HIV/AIDS - Abraham Gainau; Louisa Nindya Watratan; Elgita Clara Tahitu (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
HIV/AIDS remains an infectious disease that poses a global health challenge in both developed and developing countries. The rising number of HIV/AIDS cases among adolescents indicates that this age group is highly vulnerable to infection due to physical, psychological, and social changes during their developmental stage. Adequate knowledge of HIV/AIDS plays a vital role in preventing and controlling its transmission among adolescents. This study aims to describe the level of knowledge about HIV/AIDS among students at SMP Negeri 4 Seram Barat in 2025. This research is a quantitative descriptive study using a cross-sectional design. Samples were obtained through simple random sampling, involving 65 students. Data were collected using a structured questionnaire and analyzed bivariately to present the frequency distribution of knowledge levels. The results showed that 11 respondents (16.9%) had good knowledge, 42 (64.6%) had moderate knowledge, and 12 (18.5%) had low knowledge. It can be concluded that most students have moderate knowledge of HIV/AIDS; however, enhanced health education is needed to improve understanding of disease prevention and transmission.